Kesulitan Membaca Peserta Didik dalam Pembelajaran: Systematic Literature Review - Muna Fauziah; Fani Fitri Desiani (Lembaga Einstein College, 2024)
This research aims to determine students' reading difficulties in learning. This research is a systematic literature review research that takes secondary data. Data was collected from various databases sourced from accredited national journal articles accessed from Google Scholar. The database taken is from journals published from 2014 to 2024. The data collected is analyzed descriptively by presenting the data regularly so that it can be understood by readers. Research findings show that elementary school students' reading difficulties include: difficulty identifying/distinguishing letters; difficulty arranging letters and syllables to read a word (especially combinations of vowels and consonants); difficulty changing words; often omitting letters in word order; lack of attention to punctuation; spelling difficulties; inability to pronounce phonemes, diphthongs, double vowels, and double consonants; lack of letter pronunciation and vocabulary mastery; cannot read complete sentences; difficulty reading meaningful words; still doing deletions, reversals, insertions, word replacements while reading; as well as fluency in reading aloud and reading comprehension.